IMPLEMENTASI MANAJEMEN MUTU TERPADU DALAM MENINGKATKAN MUTU PENDIDIKAN - R. Sri Martini Meilanie; Nana Aminah (Perspektif Ilmu Pendidikan, 2009)
The main objective of this research was to describe objectively the implementation of Total Quality Management (TQM) to improve education quality. To meet the objective a case study was conducted in AlMuslimin Primary School , Tambun, Bekasi. in 200xxx. employng descriptive method. Data were collected by using interview and observation tecniqes and analyzed descriptively to answer the research questions. The research was focused to answer three research question. Beside being able to give clear and objective description of TQM implementation in AlMuslimin Primary School as the research findings, the research found that TQM could improve the eduaction quality in the school under identified certain conditions. To optimoza the quality education by using TQM, the research provided a number of recommendations.